Leveraging Corporate Social Responsibility to Strengthen Customer-Based Brand Equity in Ghana’s Hotel Industry - Francis Osei; Boadi Mercy; Collins Kankam-Kwarteng; Samuel Babae Ansong; Alfred Owusu (Journal of Social Entrepreneurship Theory and Practice, 2026)
Corporate Social Responsibility (CSR) is gaining increasing importance in the hospitality industry, particularly in emerging markets where customers are becoming more attentive to social and environmental practices. However, the influence of CSR on the components of Customer-Based Brand Equity (CBBE) has not been sufficiently examined in the Ghanaian hotel sector. This study, therefore, investigates the effect of CSR initiatives on CBBE, focusing on four key dimensions: brand awareness, brand association, perceived quality, and brand loyalty, based on Aaker’s multidimensional brand equity framework. A quantitative research approach was employed using a structured questionnaire administered to 249 hotel customers in Kumasi, Ghana. The collected data were analyzed using SPSS and SmartPLS to test the hypothesized relationships between CSR and the four dimensions of CBBE. The findings reveal that CSR has a statistically significant and positive effect on brand awareness, brand association, perceived quality, and brand loyalty. These results suggest that CSR initiatives can strengthen customers’ perceptions of hotel brands and enhance overall brand equity in the hospitality context. Nevertheless, the study is limited to the hotel sector in Kumasi, Ghana, which restricts the broader generalizability of the findings. Future research could extend this work by examining other geographic regions, different hotel categories, and additional variables such as customer satisfaction or brand meaning to develop a more comprehensive model. This study contributes to the literature by empirically linking CSR to the development of customer-based brand equity in the Ghanaian hospitality industry. By integrating CSR into Aaker’s brand equity model, the study offers both theoretical insights and practical implications, highlighting how hotel managers can leverage CSR as a strategic tool to build strong, loyal brands in socially conscious markets.